Chemical synthesis of C6-tetrazole ᴅ-mannose building blocks and access to a bioisostere of mannuronic acid 1-phosphate - Dimitriou, Eleni; Miller, Gavin J. (Beilstein Journal of Organic Chemistry, 2021)
Alginate is a biocompatible and industrially relevant polysaccharide that derives many of its important properties from the charged carboxylate groups within its polyuronic acid backbone. The design and inclusion of isosteric replacements for these carboxylates would underpin provision of new oligo-/polysaccharide materials with alternate physicochemical properties. Presented herein is our synthesis of mannuronic acid building blocks, appropriately modified at the carboxylate C6 position with a bioisosteric tetrazole. Thioglycosides containing a protected C6-tetrazole are accessed from a C6-nitrile, through dipolar cycloaddition using NaN3 with n-Bu2SnO. We also demonstrate access to orthogonally C4-protected donors, suitable for iterative oligosaccharide synthesis. The development of these building blocks is showcased to access anomeric 3-aminopropyl- and 1-phosphate free sugars containing this non-native motif.
Keywords: alginate; glycosyl 1-phosphate; non-native monosaccharide; tetrazole; uronate

(untitled) - Lee, K. Y.; Mooney, D. J. (Prog. Polym. Sci., 2012)

(untitled) - Ertesvåg, H. (Front. Microbiol., 2015)

(untitled) - Sabra, W.; Zeng, A.-P.; Deckwer, W.-D. (Appl. Microbiol. Biotechnol., 2001)

(untitled) - Jia, J.; Richards, D. J.; Pollard, S.; Tan, Y.; Rodriguez, J.; Visconti, R. P.; Trusk, T. C.; Yost, M. J.; Yao, H.; Markwald, R. R.; Mei, Y. (Acta Biomater., 2014)

(untitled) - Sun, J.; Tan, H. (Materials, 2013)

(untitled) - Zhang, Q.; van Rijssel, E. R.; Walvoort, M. T. C.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Dinkelaar, J.; van den Bos, L. J.; Hogendorf, W. F. J.; Lodder, G.; Overkleeft, H. S.; Codée, J. D. C.; van der Marel, G. A. (Chem. – Eur. J., 2008)

(untitled) - van den Bos, L. J.; Dinkelaar, J.; Overkleeft, H. S.; van der Marel, G. A. (J. Am. Chem. Soc., 2006)

(untitled) - Pan, D.; Zhang, L.; Hua, Q.; Yang, Y. (Org. Biomol. Chem., 2019)

(untitled) - Codée, J. D. C.; van den Bos, L. J.; de Jong, A.-R.; Dinkelaar, J.; Lodder, G.; Overkleeft, H. S.; van der Marel, G. A. (J. Org. Chem., 2009)

(untitled) - Dimitriou, E.; Miller, G. J. (Org. Biomol. Chem., 2019)

(untitled) - Ostrovskii, V. A.; Trifonov, R. E.; Popova, E. A. (Russ. Chem. Bull., 2012)

(untitled) - Walvoort, M. T. C.; van den Elst, H.; Plante, O. J.; Kröck, L.; Seeberger, P. H.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Angew. Chem., Int. Ed., 2012)

(untitled) - Lassalas, P.; Gay, B.; Lasfargeas, C.; James, M. J.; Tran, V.; Vijayendran, K. G.; Brunden, K. R.; Kozlowski, M. C.; Thomas, C. J.; Smith, A. B., III; Huryn, D. M.; Ballatore, C. (J. Med. Chem., 2016)

(untitled) - Wittenberger, S. J.; Donner, B. G. (J. Org. Chem., 1993)

(untitled) - Mende, M.; Nieger, M.; Bräse, S. (Chem. – Eur. J., 2017)

(untitled) - Mitra, B.; Mukherjee, S.; Pariyar, G. C.; Ghosh, P. (Tetrahedron Lett., 2018)

(untitled) - Ostrovskii, V. A.; Koren, A. O. (Heterocycles, 2000)

(untitled) - Ahmadipour, S.; Pergolizzi, G.; Rejzek, M.; Field, R. A.; Miller, G. J. (Org. Lett., 2019)

(untitled) - Beswick, L.; Dimitriou, E.; Ahmadipour, S.; Zafar, A.; Rejzek, M.; Reynisson, J.; Field, R. A.; Miller, G. J. (ACS Chem. Biol., 2020)

(untitled) - Beswick, L.; Ahmadipour, S.; Dolan, J. P.; Rejzek, M.; Field, R. A.; Miller, G. J. (Carbohydr. Res., 2019)

(untitled) - Ahmadipour, S.; Beswick, L.; Miller, G. J. (Carbohydr. Res., 2018)

(untitled) - Ahmadipour, S.; Miller, G. J. (Carbohydr. Res., 2017)